Učinki "svete polomije" na zaupanje v cerkev - Smrke, Marjan (Teorija in praksa, 2012)
The 2011 Slovenian Public Opinion (SJM) research showed that trust in the Roman Catholic Church in Slovenia has fallen to an all-time low in the country's post-independence era: only 25% of Slovenians expressed a great deal or quite a lot of trust in the Church. This article considers how the Catholic Church's social power has been impacted by the so-called "holy crash"; namely, the 2010 collapse of the archdiocese of Maribor's financial empire and its investments and interests in various enterprises controlled through its Gospodarstvo Rast financial firm. It reveals the fact that in recent years trust has declined the most in the Podravje and Koroška regions of Slovenia, both of which lie within the Maribor archdiocese. This decline intrust supports the central hypothesis that the scandal and secrecy surrounding the collapse have negatively impacted trust. The article further establishes that trust in the Church has declined among regular churchgoers, although to a smaller extent than among less committed adherents to the faith. In the conclusion, this article reflects on the wider social consequences of the crash and diminished trust in the Catholic Church among Slovenians. Indeed, both contribute to neo-secularisation, i.e. the decline ofreligious authority, and in the medium term considerably affect realisation of those Church-sponsored projects designed towards the pillarisation of Slovenian society
Keywords: Cerkev in družba; Church and society; Christian church; Krščanska cerkev; Economic crises; Ekonomske krize; Afere; Affairs; Trust; Zaupanje; Secularization; Sekularizacija; Slovenia; Slovenija; cerkev; Church; javno mnenje; socialni kapital